BRAF-mediated brain tumors in adults and children: A review and the Australian and New Zealand experience - Trinder, Sarah M.; McKay, Campbell; Power, Phoebe; Topp, Monique; Chan, Bosco; Valvi, Santosh; McCowage, Geoffrey; Govender, Dinisha; Kirby, Maria; Ziegler, David S.; Manoharan, Neevika; Hassall, Tim; et al. (Frontiers in Oncology, 2023)
The Mitogen-Active Protein Kinase (MAPK) pathway signaling pathway is one of the most commonly mutated pathways in human cancers. In particular, BRAF alterations result in constitutive activation of the RAF-ERK-MAPK significant pathway leading to cellular proliferation, survival and dedifferentiation. The role of BRAF mutations in oncogenesis and tumorigenesis has spurred the development of targeted agents, which have been successful in treating many adult cancers. Recently, there has been recognition that MAPK dysregulation is almost universally present in glioma. Despite advances in other cancer types, the morbidity and survival outcomes of patients with glioma have remained relatively stagnant. The molecular characterization of gliomas has aided prognostication and offered opportunities for clinical trials testing targeted agents. The use of targeted therapies in this disease represents a paradigm shift, although the biochemical complexities has resulted in unexpected challenges in the development of effective BRAF inhibitors. Despite these challenges, there is promising data to support the use of BRAF inhibitors alone and in combination with MEK inhibitors for patients with both low-grade and high-grade glioma. Safety and efficacy data demonstrates that many of the toxicities of these targeted agents are tolerable whilst offering objective responses. Newer clinical trials will examine the use of these therapies in the upfront setting. Appropriate duration of therapy and durability of response remains unclear in the glioma patient cohort. Longitudinal efficacy and toxicity data is needed. Furthermore, access to these medications remains challenging outside of clinical trials in Australia and New Zealand. Compassionate access is limited and advocacy for mechanism of action-based drug approval is ongoing.